2015
DOI: 10.1007/s00264-015-2798-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients with thoracic trauma and concomitant spinal cord injury have a markedly decreased mortality rate compared to patients without spinal cord injury

Abstract: Our results demonstrate that patients with thoracic trauma and concomitant SCI had markedly decreased mortality compared to patients without SCI, even after adjusting for age, sex, injury severity, comorbidities and pneumonia infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Several other studies already had assumed a prognostic advantage of SCI patients in severe trauma and inflammation. Bertling et al 14 were able to show that patients with thoracic trauma and SCI had a lower mortality rate as compared to patients without SCI. In this single-center retrospective, matched pair analysis including age, ISS, and comorbidity index, 6 (11.1%) of 54 SCI patients died during the hospital stay, whereas 19 (31.5%) of 61 non-SCI patients deceased during hospitalization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several other studies already had assumed a prognostic advantage of SCI patients in severe trauma and inflammation. Bertling et al 14 were able to show that patients with thoracic trauma and SCI had a lower mortality rate as compared to patients without SCI. In this single-center retrospective, matched pair analysis including age, ISS, and comorbidity index, 6 (11.1%) of 54 SCI patients died during the hospital stay, whereas 19 (31.5%) of 61 non-SCI patients deceased during hospitalization.…”
Section: Discussionmentioning
confidence: 97%
“…[9][10][11][12][13] This may ultimately result in an increased rate of infection and mortality following multiple trauma. However, a recent study by Bertling et al 14 revealed a lower mortality rate for patients with SCI compared to a control group of multiple injured patients without SCI.…”
Section: Introductionmentioning
confidence: 93%
“…The Charlson Comorbidity Index (CCI) was calculated to measure disease burden, using the updated version from 2010 (Quan et al, 2011). CCI have been used in patients with SCI (Bertling et al, 2016;Burns, Weaver, Chin, Svircev, & Carbone, 2016). Each comorbid condition was weighted according to the related risk of mortality in one year: congestive heart failure -2 points; dementia -2 points; chronic pulmonary disease -1 point; rheumatologic disease -1 point; mild liver disease -2 points/ moderate or severe liver disease -4 points; diabetes with chronic complications -1 point; hemiplegia or paraplegia -2 points; renal disease -1 point; any malignancy, including leukaemia and lymphoma -2 points/ metastatic solid tumour -6 points, acquired immunodeficiency syndrome or human immunodeficiency virus -4 points (Quan et al, 2011).…”
Section: Data Collectionmentioning
confidence: 99%